2021
DOI: 10.1093/beheco/arab031
|View full text |Cite
|
Sign up to set email alerts
|

The conspecific avoidance strategies of adult female-calf humpback whales

Abstract: During migration, humpback whale (Megaptera novaeangliae) adult females and their calves use acoustic calling to help maintain contact. The signals produced by these pairs, however, may unintentionally attract nearby breeding males, which can result in interactions that have negative physical and physiological effects on the calf. Therefore, maternal females must choose the vocal and/or behavioral strategy that most effectively balances intra-pair communication with male avoidance. Here, we analyzed difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…They exhibit considerable differences in their acoustic parameters between age classes (Indeck et al, 2021) and the variety of call types produced suggests that they may serve several potential functions, including as contact, distress, and/or nursing calls. Additionally, Videsen et al (2017) noted that adult female–calf pairs produced calls at very low levels (on average 136 and 141 dB re 1 µPa, depending on call type) compared to previously reported calls by other humpback whale groups (e.g., Dunlop et al, 2013) and suggested that these resulted in a restricted active space with a radius of only 30 m. Cryptic calling, resulting in calls that are naturally difficult to detect, has been shown to be a vocal strategy for avoiding unwanted conspecific interaction (Indeck et al, 2021). However, such low‐level calls would be particularly susceptible to acoustic masking from anthropogenic activities, increasing the risk that a female may lose acoustic contact with her calf.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…They exhibit considerable differences in their acoustic parameters between age classes (Indeck et al, 2021) and the variety of call types produced suggests that they may serve several potential functions, including as contact, distress, and/or nursing calls. Additionally, Videsen et al (2017) noted that adult female–calf pairs produced calls at very low levels (on average 136 and 141 dB re 1 µPa, depending on call type) compared to previously reported calls by other humpback whale groups (e.g., Dunlop et al, 2013) and suggested that these resulted in a restricted active space with a radius of only 30 m. Cryptic calling, resulting in calls that are naturally difficult to detect, has been shown to be a vocal strategy for avoiding unwanted conspecific interaction (Indeck et al, 2021). However, such low‐level calls would be particularly susceptible to acoustic masking from anthropogenic activities, increasing the risk that a female may lose acoustic contact with her calf.…”
Section: Introductionmentioning
confidence: 66%
“…Here, we found that this risk was greatest for adult female–calf humpback whale pairs during periods of “resting/milling” as compared to periods of “travelling.” As expected, these pairs called significantly more often when resting; however, they did not increase their call levels between behavioral states. Due to their consistently low levels, the majority of adult female–calf calls were estimated to reach an SNR of 0 before 2 km, limiting their detectability by nearby conspecifics (Indeck et al, 2021). Therefore, we show that these pairs balance their need to maintain contact when separated (i.e., increased calling) with their effort to simultaneously maintain acoustic crypsis (i.e., quiet calling).…”
Section: Discussionmentioning
confidence: 99%
“…This includes humpback whales and grey whales, which both visit seasonal calving sites in shallow, near shore environments [ 59 ]. Acoustic crypsis in signal production amplitude, similar to that of right whales, has been observed in migrating humpback whale mother–calf pairs in Australia [ 4 , 26 ]. Additionally, humpback whale mother–calf pairs have been observed moving to shallower waters and spending more time near the surface when there are breeding males nearby [ 4 ], behaviours which could allow mother–calf pairs to avoid acoustic detection by conspecifics.…”
Section: Discussionmentioning
confidence: 99%
“…Acoustic crypsis in signal production amplitude, similar to that of right whales, has been observed in migrating humpback whale mother–calf pairs in Australia [ 4 , 26 ]. Additionally, humpback whale mother–calf pairs have been observed moving to shallower waters and spending more time near the surface when there are breeding males nearby [ 4 ], behaviours which could allow mother–calf pairs to avoid acoustic detection by conspecifics. Grey whales are known to nurse their calves in shallow lagoons and research has suggested that avoidance of killer whale predators may drive migration to these habitats [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation